AffectTracker: real-time continuous rating of affective experience in immersive virtual reality - Fourcade, Antonin; Malandrone, Francesca; Roellecke, Lucy; Ciston, Anthony; Mooij, Jeroen de; Villringer, Arno; Carletto, Sara; Gaebler, Michael (Frontiers in Virtual Reality, 2025)
Subjective experience is key to understanding affective states, characterized by valence and arousal. Traditional experiments using post-stimulus summary ratings do not resemble natural behavior. Fluctuations of affective states can be explored with dynamic stimuli, such as videos. Continuous ratings can capture moment-to-moment affective experience, however the rating or the feedback can be interfering. We designed, empirically evaluated, and openly share AffectTracker, a tool to collect continuous ratings of two-dimensional affective experience (valence and arousal) during dynamic stimulation, such as 360-degree videos in immersive virtual reality. AffectTracker comprises three customizable feedback options: a simplified affect grid (Grid), an abstract pulsating variant (Flubber), and no visual feedback. Two studies with healthy adults were conducted, each at two sites (Berlin, Germany, and Torino, Italy). In Study 1 (Selection: n = 51), both Grid and Flubber demonstrated high user experience and low interference in repeated 1-min 360-degree videos. Study 2 (Evaluation: n = 82) confirmed these findings for Flubber with a longer (23-min), more varied immersive experience, maintaining high user experience and low interference. Continuous ratings collected with AffectTracker effectively captured valence and arousal variability. For shorter, less eventful stimuli, their correlation with post-stimulus summary ratings demonstrated the tool’s validity; for longer, more eventful stimuli, it showed the tool’s benefits of capturing additional variance. Our findings suggest that AffectTracker provides a reliable, minimally interfering method to gather moment-to-moment affective experience also in immersive environments, offering new research opportunities to link affective states and physiological dynamics.